Managing Generation Z in the Restaurant Sector: Cross-Case Human Resource Management Challenges in the Sanur Tourism Area, Denpasar - Arcana, I Nyoman; Muliana, I Wayan; Pastini, Ni Wayan; Budiani, Ni Putu Ariesta; Sudiparwati, Putu Ayu (Jurnal Ilmiah Hospitality Management, 2025)
The restaurant sector in tourism areas such as Sanur, Bali faces ongoing human resource challenges, including high turnover, recruitment difficulties, and limited training effectiveness. These issues vary across hotel restaurants, fine-dining independent restaurants, and casual restaurants due to differences in management models and market positioning. This study aims to identify key human resource challenges, analyse differences in management approaches, and propose strategies to support workforce stability and operational efficiency. Using a descriptive qualitative approach, the research was conducted in three restaurant types in Sanur between July and October 2025.  Primary data were gathered through participatory observation complemented by in-depth interviews involving managers and employees from three categories of restaurants. The findings indicate distinct human resource management patterns and retention strategies, ranging from global career-oriented systems to family-based organizational cultures. This study confirms that organizational culture and Generation Z characteristics are key determinants in workforce retention strategies within tourism destinations.